1998
DOI: 10.1091/mbc.9.10.2973
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Localization Elements ofXenopus laevisU3 Small Nucleolar RNA

Abstract: The Nucleolar Localization Elements (NoLEs) of Xenopus laevis U3 small nucleolar RNA (snoRNA) have been defined. Fluorescein-labeled wild-type U3 snoRNA injected into Xenopus oocyte nuclei localized specifically to nucleoli as shown by fluorescence microscopy. Injection of mutated U3 snoRNA revealed that the 5Ј region containing Boxes A and AЈ, known to be important for rRNA processing, is not essential for nucleolar localization. Nucleolar localization of U3 snoRNA was independent of the presence and nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 63 publications
1
49
1
Order By: Relevance
“…The box CϩD sequences, together with a stem structure that normally brings them together in the snoRNA secondary structure are the only elements essential for the synthesis and stability of this class of snoRNA, and their presence is the only feature that is clearly conserved among the box CϩD snoRNAs (Baserga et al+, 1991;Huang et al+, 1992;Caffarelli et al+, 1996;Watkins et al+, 1996;Xia et al+, 1997)+ A simple model for the involvement of Nop58p in snoRNA stability is through protection from the exonucleolytic activities that normally generate the mature ends+ If so, the alteration in the 39 end of U24 on depletion of Nop58p suggests that this interaction might be via binding to the conserved box D at the 39 end of the snoRNAs+ Curiously, inspection of the 39 end of U24 (CUGAUGAAU OH ) (Qu et al+, 1995) reveals the presence of a consensus box C motif (UGAUGA), partially overlapping the box D element (CUGA)+ We speculate that on depletion of Nop58p, the putative box C binding protein(s), which normally binds to the 59 end of the snoRNA, also binds to the cryptic 39 box C element+ This might confer extra protection to U24 and explain why this species is more resistant to Nop58p depletion+ During depletion of Nop58p, Nop1p was reported to be delocalized to the nucleoplasm and cytoplasm (Wu et al+, 1998)+ In the conditions used (up to 12 h in glucose medium) the snoRNAs were presumably strongly depleted+ This indicates that Nop1p does not localize to the nucleolus on its own, but rather is localized to and/or anchored to the nucleolus in association with snoRNPs+ The association of the box CϩD snoRNAs with the nucleolus does not require complementarity to the pre-rRNA (Lange et al+, 1998b)+ Instead, both snoRNA stability and nucleolar targeting require the conserved box CϩD elements and the terminal stem (Lange et al+, 1998a(Lange et al+, , 1998cSamarsky et al+, 1998)+ It seems probable that Nop58p stabilizes the snoRNAs via binding to one or both of these sequence elements and is, therefore, a good candidate to provide the nucleolar targeting signals+ Testing of this hypothesis will require the separation of the role of Nop58p in snoRNA stability from its putative targeting function+…”
Section: Discussionmentioning
confidence: 99%
“…The box CϩD sequences, together with a stem structure that normally brings them together in the snoRNA secondary structure are the only elements essential for the synthesis and stability of this class of snoRNA, and their presence is the only feature that is clearly conserved among the box CϩD snoRNAs (Baserga et al+, 1991;Huang et al+, 1992;Caffarelli et al+, 1996;Watkins et al+, 1996;Xia et al+, 1997)+ A simple model for the involvement of Nop58p in snoRNA stability is through protection from the exonucleolytic activities that normally generate the mature ends+ If so, the alteration in the 39 end of U24 on depletion of Nop58p suggests that this interaction might be via binding to the conserved box D at the 39 end of the snoRNAs+ Curiously, inspection of the 39 end of U24 (CUGAUGAAU OH ) (Qu et al+, 1995) reveals the presence of a consensus box C motif (UGAUGA), partially overlapping the box D element (CUGA)+ We speculate that on depletion of Nop58p, the putative box C binding protein(s), which normally binds to the 59 end of the snoRNA, also binds to the cryptic 39 box C element+ This might confer extra protection to U24 and explain why this species is more resistant to Nop58p depletion+ During depletion of Nop58p, Nop1p was reported to be delocalized to the nucleoplasm and cytoplasm (Wu et al+, 1998)+ In the conditions used (up to 12 h in glucose medium) the snoRNAs were presumably strongly depleted+ This indicates that Nop1p does not localize to the nucleolus on its own, but rather is localized to and/or anchored to the nucleolus in association with snoRNPs+ The association of the box CϩD snoRNAs with the nucleolus does not require complementarity to the pre-rRNA (Lange et al+, 1998b)+ Instead, both snoRNA stability and nucleolar targeting require the conserved box CϩD elements and the terminal stem (Lange et al+, 1998a(Lange et al+, , 1998cSamarsky et al+, 1998)+ It seems probable that Nop58p stabilizes the snoRNAs via binding to one or both of these sequence elements and is, therefore, a good candidate to provide the nucleolar targeting signals+ Testing of this hypothesis will require the separation of the role of Nop58p in snoRNA stability from its putative targeting function+…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that U3-55k is also localized in the nucleoli of multiple cell types (Figs 2B and C and 6D; 45). The sequence elements involved in the localization of U3 RNA to nucleoli have been investigated (31,69,70). We have found that while the Box B/C motif of U3 is involved in the retention of the RNA in the nucleus, it is neither required nor sufficient for nucleolar localization (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have demonstrated that snoRNAs with substitution mutations disrupting the terminal stem cannot reach nucleolus and are accumulated in so-called coiled bodies (Narayanan et al, 1999); according to alternative data such RNAs are able to reach the nucleolus (Lange et al, 1998). Naturally occurring snoRNAs lacking the terminal stem in mature state are probably transferred into nucleolus as a longer IR-containing precursors.…”
Section: Resultsmentioning
confidence: 99%